Online lecturers evaluation system - Mariani Mohd Rajab (Universiti Malaysia Perlis, 2008)
A Lecturers’ web questionnaire generator is described here. It will be an application that makes easier and forward making and processing of dynamic web questionnaire forms and showing results in graphic form. It will be a flexible application for the use by either the end users (students) or by administrators. The main technology that will be used to develop this application is PHP (Programming language), MySQL (database engine) and Apache (Web server). The system will have two interfaces, one meant for the end users (Students), and the other dedicated solely for the admin whom is interested about analyzing the input data. Methodology that use in this project is prototype methodology. Hardware required in this project at least two computers, one for server and the other for user. Finally, the product of this project is student can vote their lecturers not longer manual but online.